Implementasi Algoritma Random Walk untuk Procedural Generation dalam Genre Game Dungeon Crawler 2D - Arifudin, Dani; Ringi Rizky, Dhipa; Dwi Riyanto, Andi; Suliswaningsih (Infotekmesin, 2024)
The use of algorithms to produce content through procedural generation is an attractive alternative in game development. However, it should be noted that there are various types of algorithms with varying results, as well as their suitability for 2D/3D game types. Random walk is a simple algorithm that is often used in procedural generation. This algorithm works on discrete or continuous space, from an initial position and moves by taking a random direction at each step. The Dungeon Crawler game genre is a type of game that can utilize procedural generation. A game genre that developed from the RPG genre, focusing on the exploration of mazes or dungeons that are often randomized and full of various obstacles. This genre offers several interesting features, such as collecting exploration rewards, solving puzzles, and finding a way out. This research uses GDLC as a system development method based on Windows PC devices. The test results using the Black Box method can be said to be successful because the game succeeded in creating levels automatically by implementing the Random walk algorithm.